Improving Students' English Language Skills Through Listening to English-Language Podcasts - Anggraini Anggraini (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Various dynamic approaches have emerged due to advances in computer technology in supporting language learning skills. One innovative method in English language learning is the use of audio media such as podcasts. Podcasting is one of the latest tools employed by educators to deliver educational content and promote learning beyond the classroom. This study aims to describe the influence of listening to English-language podcasts on improving students' English language skills, particularly in the aspects of listening, vocabulary acquisition, and pronunciation. The research method employed is a literature review with a descriptive qualitative approach. The findings indicate that podcasts can serve as an effective, flexible learning medium capable of stimulating English language skills holistically. It is hoped that the results of this study can serve as a foundation for the development of digital media-based learning strategies.